The Mini Nutritional Assessment-Short Form as a predictor of nursing home mortality in Japan: A 30-month longitudinal study. (January 2020) - Motokawa, Keiko; Yasuda, Jun; Mikami, Yurie; Edahiro, Ayako; Morishita, Shiho; Shirobe, Maki; Ohara, Yuki; Nohara, Kanji; Hirano, Hirohiko; Watanabe, Yutaka
Highlights: We examined residents' MNA®-SF score & 30-month mortality in Japanese nursing homes. During the study, 157 (42.8%) participants died. MNA®-SF scores were significantly lower in the deceased residents than survivors. After adjusting for confounders, MNA®-SF score was associated with mortality. MNA®-SF is an effective predictor of mortality in nursing homes in Japan. Abstract: Objectives: We examined whether the Mini Nutritional Assessment-Short Form (MNA®-SF) predicted mortality in 367 nursing home residents (82% women; mean age = 84.4 ± 8.5 years) in Japan. Measurements: We examined participants' basic characteristics (sex, age, height, weight, and medical history), the Barthel index (BI), clinical dementia rating (CDR), and six items of the MNA®-SF. The association between the MNA®-SF and 30-month mortality was assessed using a Cox proportional regression analysis. Results: During the study, 157 (42.8%) participants died. MNA®-SF scores in the Survival group were significantly higher than in the Death group (9.4 ± 2.1 vs. 8.4 ± 2.3, respectively; p  <  .001). After adjusting for age, sex, history of aspiration pneumonia, BI, and CDR, MNA®-SF scores were significantly associated with 30-month mortality (hazard ratio: 0.89, 95% confidence interval: 0.82–0.97, p  =  .005). Conclusion: The MNA®-SF was an effective predictor of mortality among nursing home residents in Japan, even after adjusting for potential confounders. These results indicate that periodically evaluating nutritional status using the MNA®-SF, and nutritional interventions according to status, may result in maintenance and improvement of nutritional status, as well as lead to reduced mortality.